Rancang Bangun Mesin Pemipil Jagung Menggunakan Sistem Poros Pemipil Dengan Rantai Perontok - Rivanol Chadry; Ichlas Nur; Daddy Budiman (Politeknik Negeri Padang, 2022)
Indonesia is an agricultural country with vast agricultural land and abundant natural resources. Thus, it is not surprising that the Indonesian agricultural sector has a very important role in economic growth, because this sector has great potential in absorbing a large number of workers as well as supporting food needs. West Sumatra is one of the corn-producing provinces in Indonesia with corn production in West Sumatra Province in 2020 of 935,716 tons or 59,465 tons less than the production target of 995,201 tons. Availability of corn supplies will greatly affect the livestock industry in general. If the supply of corn raw materials experiences scarcity, it will result in stagnation in the availability of animal feed. On the contrary, with the adequacy of corn raw materials, it will encourage the smooth supply of animal feed. This means that corn is very influential on the performance of livestock development and the provision of animal protein which is much needed in improving the quality of human resources. The purpose of this research is to be able to design and manufacture a corn sheller machine. The working principle of this machine is to rotate the shaft which aims to make the corn revolution motion towards the shaft and is held by the retaining wall at the bottom which will separate the corn kernels and the cobs. The research method used is applied research method. This research started from the design of the corn sheller machine until the tool was formed, so that the following specifications were obtained: using a gasoline-fueled motor with a power of 6.5 HP, having a funnel above the side of the sheller tube, using a frame with angle iron, the sheller shaft consists of shaft with a length of 870 mm and a diameter of 25.4 mm and there are 13 threshing chains on the side of the shaft with a width of 20 mm and each chain has a length of 180 mm, has a corn screen that functions as a retaining wall and a corn separator filter with cobs, There are 2 pieces pulley, namely the pulley on the motor and sheller shaft, and uses a belt with size A-44.